Эволюция связки орбит в метеорном рое Геминид - Крамер, Е.Н.; Шестака, И.С. (Кинематика и физика небесных тел, 1985)
На основании фотографических наблюдений метеорного потока Геминид исследуется эволюция роя. Анализ фазовых расстояний орбит в рое и дисперсии элементов орбит для различных эпох приводит к выводу о том, что рой Геминид возник сравнительно недавно — не ранее 1000 лет назад, а порождаемый им метеорный поток доступен наблюдениям только при одном сближении с Землей на протяжении 200—300 лет. On the basis of photographic observations of Geminids meteor stream evolution of the swarm is investigated. The analysis of the orbital phase distances in the swarm and of the dispersion of orbital elements for different epochs leads to the following conclusions: a) the Geminids swarm originated not earlier than 1000 year ago; b) its meteor stream may be observed only during one approach to the Earth over 200— 300 years.